Improving the methyl lactate yield from glucose over Sn–Al-Beta zeolite by catalyst promoters - Aho Atte; Kumar Narendra; Eränen Kari; Lassfolk Robert; Mäki-Arvela Päivi; Salmi Tapio; Peurla Markus; Angervo Ilari; Hietala Jukka; Murzin Dmitry Yu (Elsevier B.V., 2025)
Sn–Al-Beta zeolite was prepared through a hydrothermal method and further modified by alkali and alkaline earth (e.g. Sr and Ba) metals not practically altering the textural properties of the catalyst. The catalytic materials were tested in glucose transformation to methyl lactate in a batch reactor at 180 °C allowing to correlate catalytic activity and selectivity with the strength and type of acid sites. The results showed that by suppressing the Brønsted acidity of the modified catalyst with different promoters the yield of methyl lactate can be increased from ca. 20% to over 50%.